Chronic Diseases as a Predictor for Severity and Mortality of COVID-19: A Systematic Review With Cumulative Meta-Analysis - Geng, JinSong; Yu, XiaoLan; Bao, HaiNi; Feng, Zhe; Yuan, XiaoYu; Zhang, JiaYing; Chen, XiaoWei; Chen, YaLan; Li, ChengLong; Yu, Hao (Frontiers in Medicine, 2021)
Introduction: Given the ongoing COVID-19 pandemic and the consequent global healthcare crisis, there is an urgent need to better understand risk factors for symptom deterioration and mortality among patients with COVID-19. This systematic review aimed to meet the need by determining the predictive value of chronic diseases for COVID-19 severity and mortality. Methods: We searched PubMed, Embase, Web of Science, and Cumulative Index to Nursing and Allied Health Complete, to identify studies published between December 1, 2019 and June 12, 2020. Eighty-six observational studies from 13 countries involving 49,975 patients were included. We assessed risk of bias of the included studies and performed a meta-analysis. Results: We found that among COVID-19 patients, hypertension was the most common condition and was associated with higher severity, intensive care unit (ICU) admission, acute respiratory distress syndrome, and mortality. Chronic obstructive pulmonary disease was the strongest predictor for COVID-19 severity, admission to ICU, and mortality while asthma was associated with a reduced risk of COVID-19 mortality. Patients with obesity were at a higher risk of experiencing severe symptoms of COVID-19. Hyperlipidemia was correlated with increased severity and mortality of COVID-19. Patients with cerebrovascular disease, chronic liver disease, chronic renal disease, or cancer were more likely to become severe COVID-19 cases and had greater probability of mortality. Conclusions: COVID-19 patients with chronic diseases were more likely to experience severe symptoms and ICU admission and faced a higher risk of mortality. Aggressive strategies to combat the COVID-19 pandemic should target patients with chronic diseases as a priority.